INFLUENCE OF COST OF EDUCATION ON TRANSITION RATES FROM PRIMARY TO SECONDARY SCHOOLS INKENYA:A CASE OF MACHAKOS SUB-COUNTY - Mwikya, Veronica Nduku; Cheloti, Selpher K.; Mulwa, David (International Journal of Economics, Commerce and Management, 2019)
The purpose of this study was to investigate the influence of cost of education on transition rates from primary to secondary schools in Kenya; a case of Machakos sub-county. The study was guided by the following objectives;to determine the average cost of putting a leaner in school; asses the rate at which cost of education affect retention rates in schools and determine the rate at which cost of education influence transition rate from primary to secondary school in Machakos sub-county. The study used descriptive survey design. The target population was 135 public primary school head teachers and 145 class 8 class teachers. Simple random and purposive sampling techniques were used to identify 40 head teachers and 40 class teachers as respondents for the study. The sample size was. Questionnaires were used to collect data. Validity and reliability of the instruments was ascertained.The study found that cost of education, significantly influence the transition rate from primary school to secondary schools in Machakos Sub-County.The study recommended that government should increase education subsidies to cushion parents from extra levies charged by schools. Sub county education office should come up with practical measures to sensitize the parentson the importance of education in order to change their attitude. Parents should be taught various income generating activities so as to make them financially stable as this will reduce dependency syndrome and enable them cater for both family basic needsand education of their children
Keywords: Transition rate; cost of Education; Free Day Secondary Education; Kenya